Impact of Composting Food Waste with Green Waste on Greenhouse Gas Emissions from Compost Windrows. Issue 1 (2nd January 2019) - Williams, Sequoia R.; Zhu-Barker, Xia; Lew, Stephanie; Croze, Benjamin James; Fallan, Kenna R.; Horwath, William R.
Abstract: Windrow composting of green waste as an alternative to green waste disposal in landfills requires an understanding of the impacts on greenhouse gas (GHG) emissions and the development of effective and efficient management strategies to reduce these emissions. The addition of food waste to green waste compost operations is becoming more common, but its effect on GHG emissions is less understood. As more food waste diversion occurs as a result of recent implementation of climate smart policies in California, more information is needed to address the sustainability of composting different combinations of waste types. We monitored GHG emissions from compost windrows comprised of green waste alone and a green/food waste mixture (green waste : food waste = 9:1, by wet weight) at the University of California, Davis Student Farm in 2016 using a modified, open, flow-through chamber technique. When comparing total emissions of nitrous oxide (N2 O) and methane (CH4 ), the green/food waste mixture produced 110 kg CO2 eq./ton DM (dry matter, std error = 12.2), which were slightly lower than emissions produced by the green waste alone (152 kg CO2 eq./ton DM, std error = 15.9). Methane was a large contributor to global warming potential (GWP) of both composting treatments, suggesting that management practices that optimize porosity and air flow in compost piles are promising in reducing emissions from both green waste and green/food waste mixtures.